Potential of polyester fibrous materials in interior dividing walls - Velosa, J. C. (2012)
In order to save material and energy, an increased growth can be seen in recent times on the use of low cost and light weight solutions for interior diving walls of buildings. An alternative to more commonly used plaste rboard panels, fiber cement panels, wood and cement agglomerate, OSB panels, etc., composite pan els based on non-woven fabrics have been developed in this research work. Geo-textiles made from polyester and polypropylene yarns were consolidated using compression molding technique varying th e various structural and process parameters such as number of layers, compression time, temperatur e and pressure. Taguchi method was used to design the experiments as well as to understand the in fluence of various parameters on tensile and flexural strengths and, to optimize them in order to m aximize these properties.